Choreographing the nonhuman: cross-cultural entanglements and technologies of capture in Zuni Icosahedron's and Zurich University of the Arts' Z/Z Twin Lab. Issue 1 (2nd January 2020) - Mansbridge, Joanna Gwen
ABSTRACT: This essay analyses Z/Z Twin Lab, a telematic performance experiment that used video projections, motion capture, avatars, and live streaming to connect dancers, audiences, performance spaces, and dance pieces in Zurich, Switzerland and Hong Kong. The performances in both cities were also projected on multiple screens in Zurich's Hauptbanhoff . The collaboration brought together institutions and cities with similar infrastructures and with aims that include: facilitating the exchange of performance data; producing new platforms for performance; expanding spaces of cultural exchange; and animating interactions among cultures, bodies, technologies, and spaces in ways that position these elements not as separable entities but as entangled co-actors. The Hong Kong performance, 'Heavenly Palace, ' drew from the sixteenth-century Chinese novel, Journey to the West, while the Zurich performance, 'The Hidden Formula, ' took inspiration from Plato's Allegory of the Cave. The guiding concepts of both pieces were captivity and freedom and articulated in the question: 'Is the stage a cage?' Reading these pieces in relation to one another, this essay explores questions of capture, captivity, and the various entanglements that simultaneously enable connections and acknowledge distances. Hong Kong, as an historical entrepôt, provided a particularly resonant site for interpreting this cross-cultural experiment and its guiding concepts.